A Skin-like Self-healing and stretchable substrate for wearable electronics - Yeasmin, Rubaya; Han, Seung Ik; Duy, Le Thai; Ahn, Byungmin; Seo, Hyungtak (Chemical Engineering Journal, 2023)
Bioinspired skin-like substrates have drawn a great research interest because of their essentiality in wearable applications like electronic skin (e-skin). Yet, developing a biocompatible skin-like substrate is often challenging, especially in enabling stretchability and self-healability. Herein, the development of a multifunctional self-healing, stretchable, deformable, biocompatible, transparent, and self-adhesive composite based on networking PBS (polyborosiloxane) and Ecoflex is introduced. The developed PBS:Ecoflex composite possesses a fast self-healing capability (in 30 s at room temperature (RT)), stretchability (over 500 %), high strength, transparency (90 % of the visible light), ideal electrical insulation, and good chemical stability in various harsh conditions, including in strong acid/base solutions and different solvents. Furthermore, its thermal stability remains consistent at over 100 ℃. Altogether, those remarkable properties indicate the efficacy of using the developed composite as a mechanically skin-mimicking substrate, which is essential for numerous biomedical and wearable applications like e-skin. For the proof-of-concept, a wearable pressure sensor array is developed, and its pressure responses are monitored to validate its functioning when attached to the human skin.
Keywords: E-skin; EcoFLEX; Electronic skin; Polyborosiloxane; Research interests; Self-healing; Skin-like substrate; Stretchable; Transparent adhesives; Wearable applications; E-skin; Self-healing; Skin-like substrates; Stretchable; Wearable electronics